Physical activity and nutritional habits among Physical Education undergraduates: a cross-sectional study in Brasília - Luciana Zaranza Monteiro; Andrea Ramirez Varela; Bruno Alves Lira; Daniel Junior de Oliveira Gomes; Priscila de Souza; Leonardo Chagas Contiero; Maria de Lourdes Alves Carneiro; José Maria Thiago Bonardi (Universidade Federal de Santa Catarina, 2019)
Studies carried out in Brazil have demonstrated that the lifestyle profile of university students presents worrying deficiencies in respect to physical activity and eating habits. The aim was to evaluate the dietary habit and physical activity profile of physical education students and investigate the association between nutritional status, physical activity and eating habits. A cross-sectional design with 903 Physical Education students. All the questions were extracted from the Surveillance of Risk and Protective Factors for Chronic Diseases (Vigitel). The women were found to be more sedentary (p<0.01) and showed a higher prevalence of obesity. Those who did not practice physical activity had a high prevalence of having a chronic disease. The men had a more adequate diet and physical activity profile. Studies that focus on promoting healthy habits should be inserted early in the universities.